VALUASI TANAMAN OBAT DI DESA PETUK BUKIT KECAMATAN RAKUMPIT KOTA PALANGKA RAYA, KALIMANTAN TENGAH (Medical Plant Valuation at Petuk Bukit Village, Rakumpit Sub District, Palangka Raya City, Central Kalimantan) - Kartono Aprilianto; sari Mayawati; Nuwa Nuwa (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2019)
The aim of this study to analyze the economic value of medical plants at Petuk Bukit Village, Rakumpit Sub District, Palangka Raya City, Central Kalimantan. This research was conducted from June to August 2019 in the Rakumpit sub-district of Central Kalimantan, precisely in Petuk Bukit village. The primary data were collected using an survey method. Data analyze to predicted the economic value, income levels, and welfare level. The result showed that there are 12 types of medical plants that potentialy have economic value. The income of Petuk Bukit Village from medical plants and nonmedical plants business were obtained Rp. 3.342.420.000/year. The correlation of spearman is 0.45. The income level from medical plants is moderat to the welfare of society.